Nghiên cứu ứng dụng zeolit ZSM-5 cho phản ứng sắp xếp lại epoxit để tổng hợp andehit - Hoàng, Phan Huy; Bách, Nguyễn Xuân (Vietnam Journal of Chemistry, 2016)
This study presented the synthesis of ZSM-5 zeolite particles and their application for styrene oxide rearrangement reaction. This catalyst showed the high catalytic efficiency for liquid phase rearrangement of styrene oxide. The influences of reaction conditions such as solvent, reaction time, catalyst loading and tempreature on efficiency of styrene oxide rearrangement were also investigated. Moreover, it was remarkable that the high catalytic activity observed over ZSM-5 zeolite catalyst (conversion over 94 % after 2hrs reaction) was accompanied by the achievement of high selectivities, typically above 80 %, towards desired products with commercial applications. ZSM-5 zeolite also exhibited high efficiency in separation, recycling with long lifetime and no significant loss of catalytic activity. Keywords. ZSM-5 zeolite, epoxide, rearrangement reaction, aldehyde.